THE IMPACT OF ONLINE SOCIAL COMMUNICATION ON THE TRAINING OF SOCIAL WORKERS AND EDUCATORS (UKRAINIAN UNIVERSITIES) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
With the growing need to revise approaches to the educational process, educational institutions are increasingly turning to the digital opportunities and needs of the modern society. By closely monitoring the trends in the use of ICTs, engaging in various pilot projects for Ukraine to ensure digital literacy, develop digital competence, and use of Web 2.0 and VR social media, educational institutions are increasing their presence in the digital space of the Internet. From our point of view, this is a good basis for the declared changes in the educational paradigm at all levels of the educational process, including the training of specialists who will ensure the social, economic and cultural growth of the nation in the future. That is why it was important for us to study the theoretical database of scientific, research and pedagogical literature on the use of social media for education; compare the challenges mentioned in global trends in the use of social media and in Ukrainian practice; compare the presence and interaction of universities in social media with their value in the market of professional training of specialists, in particular, social and pedagogical profile. Based on the analysis of the above components, we have drawn conclusions about the challenges facing the Ukrainian higher education system, their root causes, and presented a number of tips and solutions that will allow universities to achieve not only a presence in the network, but also to be competitive both in the national environment and in the international arena.